The Influence of Milling and Spark Plasma Sintering on the Microstructure and Properties of the Al7075 Alloy - Molnárová, Orsolya; Málek, Přemysl; Veselý, Jozef; Minárik, Peter; Lukáč, František; Chráska, Tomáš; Novák, Pavel; Průša, Filip (Materials (Basel, Switzerland), 2018)
The compact samples of an Al7075 alloy were prepared by a combination of gas atomization, high energy milling, and spark plasma sintering. The predominantly cellular morphology observed in gas atomized powder particles was completely changed by mechanical milling. The continuous-like intermetallic phases present along intercellular boundaries were destroyed; nevertheless, a small amount of Mg(Zn,Cu,Al)₂ phase was observed also in the milled powder. Milling resulted in a severe plastic deformation of the material and led to a reduction of grain size from several µm into the nanocrystalline region. The combination of these microstructural characteristics resulted in abnormally high microhardness values exceeding 300 HV. Consolidation through spark plasma sintering (SPS) resulted in bulk samples with negligible porosity. The heat exposition during SPS led to precipitation of intermetallic phases from the non-equilibrium microstructure of both gas atomized and milled powders. SPS of the milled powder resulted in a recrystallization of the severely deformed structure. An ultra-fine grained structure (grain size close to 500 nm) with grains divided primarily by high-angle boundaries was formed. A simultaneous release of stored deformation energy and an increase in the grain size caused a drop of microhardness to values close to 150 HV. This value was retained even after annealing at 425 °C.
Keywords: gas atomized Al7075 alloy; spark plasma sintering; mechanical milling; microhardness; microstructure